Effectiveness of Rice Husk Ash and Glass Powder Waste as Partial Replacements of Cement in Concrete Construction - Pranadiarso, Tedy; Junaidi, Imam; Prasetyo, Slamet Rohadi Budi; Putra, Adinata Laksana (CIVED, 2024)
The environmental impact of cement production has drawn attention to the use of glass waste and rice husk as a partial replacement for cement in concrete. According to research, the compressive strength of concrete containing GPW and RHA can increase up to 15-20%, after which it begins to decline. The objective of this study was to analyze the effectiveness of partial replacement of cement with GPW and RHA. Some of the factors considered in this study were compressive strength and specific gravity. The proportions of GPW and RHA used were 0%, 3%, 5%, 10%, 15%. Then concrete testing was done after 7 and 28 day. The maximum 28-day concrete compressive strength result for the addition of GPW and RHA at 5% mix proportion was 33.1 Mpa. The more the proportion of GPW and RHA mixture, the more the relative specific gravity of concrete decreases. Overall, this study found that the use of GPW and RHA in concrete had a significant effect on compressive strength and specific gravity. But do not forget to pay attention to how much GPW and RHA mix needs and the quality of concrete to be achieved.